Symptoms of the lower urinary tract in pregnant women in prenatal care. - Morato, Maria Dione de Queiroz; Filoni, Eduardo; Fitz, Fátima Faní (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: During pregnancy, hormonal and mechanical factors responsible for the development and fetal growth causes changes in the genital and urinary tract of women. It is observed the appearance of urinary symptoms in pregnant women previously continents up to 74%. Evaluate urinary symptoms and knowledge of the perineal region in this period is important because they impact negatively on the quality of pregnant women’s life. Objective: To evaluate the presence of urinary symptoms and knowledge of PFM in pregnant women. Method: This is a descriptive cross-sectional study that evaluated pregnant women in care at the Basic Health Unit of Sao Paulo/SP. The characterization of women was taken by the assessment form, to measure urinary symptoms was used the International Consultation on Incontinence Questionnaire - Short Form (ICIQ - SF). On the other hand, the knowledge of PFM was evaluated by a specific questionnaire. Results: We evaluated 37 pregnant women with a mean age of 26.3 (14 and 37) years, body mass index of 28.5 (20.8 and 45.8) kg/m2 and gestational age of 24.8 (5 e 40) weeks. We observed the presence of UI in 81.1% of pregnant women, with a mean severity of 9.9 points for the ICIQ - SF. And about 54% of them knew of the existence of PFM and only 20% could locate the muscles. Conclusion: It was observed a high prevalence of urinary symptoms in women with moderate severity. Half of the women reported knowing the PFM, but only one fifth of them were able to locate them.